Morality as a part of economic cultural identity of students - Lavrenko, О. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
In the article such terms as morality, moral behavior, "the economical human being", economical culture and its cоnnection with personality mоrality are described. The research data on this problem have been analyzed.
Keywords: moral; morality; personality; economic person; economic culture